Difraksi pada Laser: Tafsir atas Cahaya di atas Cahaya? - Susilayati, Muslimah (IAIN Surakarta, 2016)
This study tries to provide an overview on the laser diffraction process which is closely correlated to hissi meaning of phrase Light upon Light in QS. An-Nur verse 35 through orthopraxy study. When light is passed through a very tiny hole, a process of diffraction can be occurred. In diffraction phenomenon, the white light will be separated according to the wavelength that is mejikuhibiniu. Based on Huygens principle, each light will be a new light source. In physics, the process of forming a new light source of the previous light source is called as